Engineering Calculus - Yahaya, Ahmad Shukri; Fadzli Mohamed Nazri; Murat, Muhamad Nazri; Irvan Dahlan; Abdul Wahab, Aeizaal Azman; Mohamad, Norizah; Ramli, Dzati Athiar; Ping, Loh Wei; Ramakrishnan, Sivakumar (Penerbit Universiti Sains Malaysia, 2017)
This book is written primarily as an introductory text aimed mainly for engineering and physical sciences students. This book is divided into three sections: Calculus of One Variable, Calculus of Multivariable and Ordinary Differential Equations. Each chapter of the book begins with a brief description of a particular topic as well as the learning outcomes. Then complete worked examples are provided for each topic. At the end of each chapter, exercises are given. This book can be used by all institutions of higher learning such as Polytechnics and Colleges as well as private and public universities. This book will also be helpful for practitioners of mathematics and researchers in various fields that require the use of mathematics.